PENGARUH KADAR SILANE SEBAGAI COUPLING AGENT TERHADAP KEKUATAN TARIK PERLEKATAN PASAK FRC E-GLASS PREFABRICATED DENGAN SEMEN IONOMER KACA TIPE 1 SEBAGAI LUTING CEMENT - , DWI AJI NUGROHO; , Dr.drg.Widjijono,S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
FRC post has been commonly cemented by resin cement, but there is not adhesive with tooth structure. Cement that has adhesive system with tooth structure is glass ionomer cement. Glass ionomer cement (GIC) cannot be adhesive with FRC post without silane coupling agent. The aim of research was to know influence silane level to tensile strength of E-glass FRC post (cementing with GIC). This research used 20 first mandibula premolar teeth. We divided into 4 groups. Group A, FRC post without silane application